2020
DOI: 10.1097/pas.0000000000001584
|View full text |Cite
|
Sign up to set email alerts
|

FUS-NFATC2 or EWSR1-NFATC2 Fusions Are Present in a Large Proportion of Simple Bone Cysts

Abstract: A simple bone cyst (SBC) is a benign bone lesion of unknown etiology. It can be differentiated from an aneurysmal bone cyst (ABC) by radiologic and histopathologic features, as well as by the absence of fusions of the USP6 gene characteristic of an ABC. In an attempt to differentiate between ABC and SBC in a recurrent bone cyst, we performed targeted RNA sequencing and found an EWSR1-NFATC2 fusion and no fusion of the USP6 gene. We subsequently analyzed additional 10 cysts, consistent with SBCs after radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
4
29
0
3
Order By: Relevance
“…Although absent in the above-mentioned mimics, the fibrin-like deposits are also absent in a subset of simple bone cysts, including seven of 15 (47%) specimens from 11 patients in the study by Pizem et al 19 and two of 10 (20%) specimens from nine patients in the current study. When the radiological and histological features are equivocal, the identification of EWSR1-NFATC2 or FUS-NFATC2 fusion in a subset of simple bone cysts may allow one to make this diagnosis.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Although absent in the above-mentioned mimics, the fibrin-like deposits are also absent in a subset of simple bone cysts, including seven of 15 (47%) specimens from 11 patients in the study by Pizem et al 19 and two of 10 (20%) specimens from nine patients in the current study. When the radiological and histological features are equivocal, the identification of EWSR1-NFATC2 or FUS-NFATC2 fusion in a subset of simple bone cysts may allow one to make this diagnosis.…”
Section: Discussionsupporting
confidence: 40%
“…NFATC2 rearrangements, which are characteristic of a subset of aggressive round cell sarcomas, [12][13][14][15][16][17][18] have been recently described in benign-appearing bone cysts. 14,19 Bode-Lesniewska et al reported a bone cyst in the humerus of a 12-year-old boy, showing aneurysmal bone cyst-like histology and harbouring an FUS-NFATC2 fusion. 14 Pizem et al identified EWSR1-NFATC2 or FUS-NFATC2 fusions in six of 11 simple bone cysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FUS-DDIT3 EWSR1-DDIT3 Alveolar Soft Part Sarcoma [139,140] t(X;17)(p11;q25) ASPCR1-TFE3 Undifferentiated Round Cell Sarcomas [4,18,91,[141][142][143][144] t(4;19)(q35;q13) t(10;19)(q26;q13) Paracentric inv(X)(p11.4p11.22) t(20;22)(q13.2;q12.2)…”
Section: Cell Cycle Dysregulation Overexpression Of Mdm2 and Cdk4unclassified
“…Kürettagen sind therapeutisch i. d. R. ausreichend, auch Spontanheilungen kommen vor [22]. Interessanterweise sind bei solitären Knochenzysten im peripheren Skelett vor Kurzem FUS-NFATC2 und EWSR1-NFATC2-Fusionstranskripte nachgewiesen worden, die zuvor nur bei hochmalignen und undifferenzierten Rundzellsarkomen bekannt waren [23]. Es bleibt abzuwarten, ob solche Veränderungen auch bei solitären Knochenzysten im Kiefer vorkommen, in jedem Fall handelt es sich um benigne Läsionen ohne Entartungspotenzial.…”
Section: Solitäre Knochenzysteunclassified